Komunikasi Sosial Pengemis Badut Jalanan - Agung Taufik Nugraha; Maman Suherman (Bandung Conference Series: Public Relations, 2022)
Abstract. The phenomenon of street clown beggars is an indication of the social problems that exist in the city of Bandung. The majority of them are based on economic deficiencies, but there are other causes as well. there are also many of the clown beggars who are based on ignorance. The purpose of this study is to find out the motives, meanings, and experiences of communication for the subject of clown beggars in responding to social communication. As well as trying to study changes in practice in begging, who were originally beggars wearing shabby clothes, now use character clown costumes which are considered more friendly to the community. This study uses a qualitative method with a phenomenological study approach. Data collection techniques were carried out by interview, observation, and documentation as well as sampling using purposive sampling technique with snowball sampling technique. The result of this study is that the subject's motives are divided into 2 categories, namely non-biological and biological motifs. The meaning of street clown beggars is intersubjective, some interpret it by entertaining themselves and others. The subject's experience of social communication in responding to forms of social communication are, firstly, social communication to fellow street clown beggars and social communication that takes place to families including parents, husband/wife and relatives. Beggar Clowns do not realize that if they change the culture of begging, they only innovate as someone who makes a living on the streets. Abstrak. Fenomena pengemis Badut Jalanan ini merupakan indikasi dari permasalahan sosial yang ada di Kota Bandung. Mayoritas dari mereka didasari karena kekurangan ekonomi, Namun ada pula penyebab lainnya. banyak juga dari pengemis badut yang didasari karena ketidak Tujuan dari penelitian ini ingin mengetahui motif, makna, dan pengalaman komunikasi bagi subjek pengemis badut dalam menanggapi komunikasi sosial. Serta berusaha mengkaji perubahan praktik dalam mengemis yang awalnya pengemis memakai baju lusuh kini menggunakan kostum badut karakter yang di anggap lebih ramah kepada masyarakat. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi fenomenologi. Teknik pengumpulan data yang dilakukan dengan wawancara, observasi, dan dokumentasi serta penarikan sample menggunakan teknik purposive sampling dengan teknik snowball sampling. Hasil penelitian ini adalah motif subjek di bagi menjadi 2 kategori, yaitu motif Non-biologis dan biologis. Makna pengemis badut jalanan bersifat intersubjektif, adapula yang memaknainya dengan menghibur diri dan orang lain. Pengalaman komunikasi sosial subjek dalam menanggapi bentuk komunikasi sosial adalah, pertama komunikasi sosial kepada sesama pengemis badut jalanan dan komunikasi sosial yang berlangsung terhadap keluarga meliputi orang tua, suami/istri dan saudara. Pengemis Badut tidak menyadari jika dirinya merubah budaya dalam mengemis, mereka hanya berinovasi sebagai seorang yang mencari nafkah di jalanan.